KEKERASAN VERBAL DALAM NOMINA MAKIAN OLEH MASYARAKAT KERINCI - Novita Sari; Agustina Agustina (Faculty of Languages and Arts, Universitas Negeri Padang, 2019)
This type of research is a qualitative study using descriptive methods. The subject of this research is words or utterances that contain invective nouns used by the community in Angkasa Pura, Sitinjau Laut District, Kerinci Regency. There are three findings in this study. First, based on its form, the verbal abuse in verbal abuse used by the community in Angkasa Pura in the Sitinjau Sea District of Kerinci Regency can be classified into two types (a) word-shaped invective noun, (b) verbal noun-shaped noun. Second, based on the type of invective noun obtained in Angkasa Pura Village, 6 species of invective noun were found, namely (1) animal name nouns, (2) plant name nouns, (3) noun names, (4) noun names, (5) ) noun name of the disease, and (6) abstract noun. Second, based on the type of invective noun obtained in Angkasa Pura Village, 6 species of invective noun were found, namely (1) animal name nouns, (2) plant name nouns, (3) noun names, (4) noun names, (5) ) noun name of the disease, and (6) abstract noun.